Epidemiologia da esquistossomose mansoni nos municípios do Parque Nacional da Serra do Cipó (ParnaCipó): desempenho de métodos de diagnóstico, monitoramento da transmissão, e de marcadores de morbidade em escolares - João Paulo dos Santos (2019)
Schistosoma mansoni infection is still a serious public health problem in Brazil. However, due to continuous chemotherapeutic interventions in endemic areas, a change in its epidemiological profile occurred. Currently, a growing number of infected individuals present with reduced to low parasite loads, making it difficult to detect eggs by the Kato-Katz (KK) method, as recommended by the World Health Organization. The main objective of this study was to carry out an epidemiological survey on schistosomiasis in schoolchildren from 6 to 14 years of age in the four municipalities (Morro do Pilar, Itambé do Mato Dentro, Serra do Cipó District - Santana do Riacho and Jaboticatubas) that make up the Serra do Cipó National Park (ParnaCipó), using different diagnostic methods: (KK, POC-CCA, and anti-SEA IgGtotal ELISA). The performance of the different methods was evaluated by comparing the KK reference test with the rapid urine test (POC-CCA), and a commercial immunoassay (IgGtotal antiSEA, Euroimmun®, Germany), which detected antibodies against soluble egg antigens of S. mansoni. The presence of other intestinal parasitoses (geohelminths and protozoa) was verified by K-K and Centrifugal-Sedimentation. The evaluation of the nutritional profile and a hemogram (erythrogram, leucogram and platelets) were verified as markers of morbidity. Samples of urine, feces and blood were collected, and positive students were re-evaluated 30 and 360 days after treatment with praziquantel (longitudinal study only in Jaboticatubas). A total of 643 schoolchildren were examined by the KK method in the initial evaluation, with a prevalence for S. mansoni of 0.59% (1/169) in the municipality of Santana do Riacho and 3.4% (9/263) in Jaboticatubas, with a reinfection rate of 1.7% (3/176). Serology for anti-SEA IgGtotal was performed in 531 samples and resulted in a 5.7% (3/53) seroprevalence in Itambé do Mato Dentro, 10.6% (13/123) in Santana do Riacho, and 17.8% % (48/269) in Jaboticatubas, which at revaluation presented 15.2% (21/138) of serological reactivity. In all four municipalities evaluated, the positivity of the POC-CCA rapid urine test was 10 to 56 times higher than the parasitological (K-K) test results. An overall prevalence of 16.7% (IC95% 13.7 - 19.9) for intestinal protozoa and 1.4% (IC95% 0.6 - 2.6) for geohelminths was also observed. In the schoolchildren examined, anemia was observed in 4.2% (22/521) and eosinophilia in 29.9% (135/452). What attracted attention in the nutritional evaluation was the high percentage of overweight schoolchildren (28.4%) (210/740 schoolchildren) and a higher proportion among female children. A growth deficit (Stature-for-age) was found in 3.9% (n = 29) with a higher proportion among male adolescents. In the comparison of the diagnostic tests for schistosomiasis, a low agreement (Kappa index) was observed between the reference method (KK) and the POC-CCA and ELISA methods with indices of κ = 0.02 and κ = 0.23, respectively. A low to moderate prevalence for schistosomiasis mansoni resulted after K-K and serological testing, respectively, suggesting that active transmission is present only in the municipality of Jaboticatubas and with indications for transmission in the District of Serra do Cipó. The high percentage of positives in POC-CCA (~ 60%) needs to be better clarified by the use of more sensitive parasitological or molecular techniques. In addition, the high rate of infection by intestinal protozoa pointed to a possible source of common contamination in schoolchildren in the Serra do Cipó district. Deviations in the nutritional profile of schoolchildren in the four municipalities were independent of parasitism, but indicated the need for integrated health actions to control overweight.